Humanitarian intervention: a comparative analysis of Iraq and Kosovo - Sherry Marlina Bt Shharuddin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
The purpose of this study is to analyse the concept of humanitarian intervention from the theoretical as well as the legalistic points of view. The study compares both Western and Muslims theories on humanitarian intervention and studies the way the theories apply in the actual conflicts in Iraq and Kosovo. The study examines the two conflicts and the circumstances that finally led to the intervention by the Western Allies. The study also analyzes the growing concern over the abuse of the concept of humanitarian intervention by studying the significant trends, the actual peacekeeping military operations and the peacekeeping process. The consequences of the intervention are also analysed briefly. The findings of the study are as follows: 1) the doctrine of humanitarian intervention is not in conflict with Islam since the main objective for intervention is saving lives; 2) the two target states had a serious humanitarian emergency involving large-scale loss of life; 3) the right to intervene was given to the Western powers only since they had the means, resources and intentions to do so; and 4) the intervention was made on behalf of those opposing the regime.